Definition, measurement, and function of pore structure dimensions of bioengineered porous bone tissue materials based on additive manufacturing: A review - Peng, Wen; Liu, Yami; Wang, Cheng (Frontiers in Bioengineering and Biotechnology, 2023)
Bioengineered porous bone tissue materials based on additive manufacturing technology have gradually become a research hotspot in bone tissue-related bioengineering. Research on structural design, preparation and processing processes, and performance optimization has been carried out for this material, and further industrial translation and clinical applications have been implemented. However, based on previous studies, there is controversy in the academic community about characterizing the pore structure dimensions of porous materials, with problems in the definition logic and measurement method for specific parameters. In addition, there are significant differences in the specific morphological and functional concepts for the pore structure due to differences in defining the dimensional characterization parameters of the pore structure, leading to some conflicts in perceptions and discussions among researchers. To further clarify the definitions, measurements, and dimensional parameters of porous structures in bioengineered bone materials, this literature review analyzes different dimensional characterization parameters of pore structures of porous materials to provide a theoretical basis for unified definitions and the standardized use of parameters.